PEMBELAJARAN PROJECT BASED LEARNING (PjBL) BERBANTUAN MEDIA KOMIK LINET (LITERASI,NUMERASI,ETNOMATEMATIKA) PADA MATERI TEOREMA PYTHAGORAS - Panglipur, Indah; Palayukan, Hersiyati; Dewanti, Lucky (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
Project-based learning (PjBL) that focuses on projects has not used much media to help the learning process. Learning media helps understanding during the learning process. Project Based Learning (PjBL) in addition to the project as a medium can be added to other learning media to improve learning outcomes and student activity. The purpose of this study is to describe the Project Based Learning (PjBL) learning process with the help of linet comic media (literacy, numeracy, and ethnomathematics) on the Pythagorean theorem. Qualitative research and descriptive approaches are used in helping to describe the results of the study. Teacher observation sheet instruments and student activities were used in data collection. The documentation method was also used to obtain project results through project reports. The conclusion that can be drawn is that project-based Based Learning (PjBL) learning with the help of using linet comic media can be concluded to be implemented well because all learning steps have been implemented. Student activity during the learning process is in the active category. Linet comics can provide an initial illustration of understanding the concept of the Phytagoras theorem applied in the building of places of worship. Recommendations are given with the expansion of material on comic media developed into digital comic media (e-comics) that are illustrative and interactive so that comic students actively learn.